Seven spiritual laws of success - "Chopra, Deepak" (New Delhi, 1996)
BASED ON NATURAL laws which govern all of creation, this book shatters the myth that success is the result of hard work, exacting plans, or driving ambition. In The Seven Spiritual Laws of Success, Deepak Chopra offers a life-altering perspective on the attainment of success: Once we understand our true nature and learn to live in harmony with natural law, a sense of well-being, good health, fulfilling relationships, energy and enthusiasm for life, and material abundance will spring forth easily and effortlessly. Filled with timeless wisdom and practical steps you can apply right away, this is a book you will want to read and refer to again and again.
Keywords: Spiritual